PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS FANTASI SISWA KELAS VII SMP NEGERI 25 PADANG - Yulita Sandra; Ayu Gustia Ningsih (EDU RESEARCH, 2024)
The Merdeka Curriculum has four language skills that must be applied, including: listening, reading, speaking, writing, presenting, and viewing. At the Junior High School (SMP) education level for Indonesian language subjects, writing skills need to be improved. This research is related to the effect of using the Think Pair Share (TPS) type cooperative learning model assisted by audiovisual media on the fantasy text writing skills of seventh grade students of SMP Negeri 25 Padang. This type of research is quantitative with experimental method. The population in this study were all seventh grade students of SMP Negeri 25 Padang in the 2024/2025 school year totaling 271 students selected by purposive sampling technique. The data in the study were the scores of students' fantasy text writing skills before and after using the Think Pair Share (TPS) type cooperative learning model assisted by audiovisual media. The results showed the effect of using the Think Pair Share (TPS) type cooperative learning model assisted by audiovisual media with an increase in the students' average score from 60.42 with Fair qualification (C) to 78.61 with Good qualification (B).